2017
DOI: 10.1111/cote.12306
|View full text |Cite
|
Sign up to set email alerts
|

Ozone utilisation for discharge printing of reactive dyed cotton

Abstract: Environmental pollution is one of the major concerns of the textile finishing sector. The reduction or substitution of the harsh chemicals used during dyeing and printing processes is necessary. In this study, the use of ozone for the discharge printing process was examined in order to substitute the use of reductive agent and caustic soda by ozone gas. The reactive dyed cotton samples were wetted by water and some selected solutions at 25%, 40% and 60% pick up were used and subjected to ozone gas treatment. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…However, contour sharpness of conventional discharge printing is much better than that of ozonation. It is not as excellent as contour sharpness of conventional discharge printing [48].…”
Section: The Photographs Of Fabrics Treated By Developed Methods (I: Omentioning
confidence: 89%
“…However, contour sharpness of conventional discharge printing is much better than that of ozonation. It is not as excellent as contour sharpness of conventional discharge printing [48].…”
Section: The Photographs Of Fabrics Treated By Developed Methods (I: Omentioning
confidence: 89%
“…Application of ozone in several domains of textile finishing has been reported. These include reduction clearing of polyester dyed with disperse dyes [5], discharge printing of reactive-dyed cotton fabrics [6], color stripping of reactive dyes from cotton textiles [7], and bleaching of raw cotton textiles [8]. The industrial application of ozone has been limited to denim and garment washing only, and its application to other areas can be a scope of study [9].…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that indigo‐dyed fabric can be decolorised by plasma treatment with the use of argon and oxygen gases . Moreover, plasma treatment can be used as a treatment method to substitute conventional stonewashing or enzymatic processes to produce a vintage look in fashion textile products, including knitted fabric and denim …”
Section: Introductionmentioning
confidence: 99%
“…9 Moreover, plasma treatment can be used as a treatment method to substitute conventional stonewashing or enzymatic processes to produce a vintage look in fashion textile products, including knitted fabric and denim. [12][13][14][15] In this study, an industrial scale plasma processing unit was used. 16 Three processing parameters, ie, air concentration, treatment duration and fabric water content, were controlled to achieve the desired decolorisation effect.…”
Section: Introductionmentioning
confidence: 99%